Animal assisted therapy and occupational therapy - Vakrinou, Paraskevi; Tzonichaki, Ioanna (Health & Research Journal, 2020)
The therapeutic relationship between the therapist and the client is considered as a primarily goal for treatment and a significant factor for the programme success. In recent years, the scientific community has brought to light more and more findings concerning the human-animal bond. Many therapists are already incorporating Animal Assisted Therapy into their program as a complementary method. The Occupational Therapist, by introducing an animal to his sessions and using it as a therapeutic tool to achieve communicative, motor, mental, emotional and sensory goals can greatly benefit the patient. Scientific studies should be carried out in Greece in order to draw conclusions that will help all members of the interdisciplinary team to integrate an animal into the pre-treatment process taking into account factors that affect both one's health and ethical use of the animal.